Identification of Groundwater Presence Using ERT (Electrical Resistivity Tomography) in Berkas Village, Teluk Segara Sub-district, Bengkulu City - Fauzi, M. Wilzam; Suhendra, Suhendra; Refrizon, Refrizon; Halauddin, Halauddin; Rabbani, M Rifqi; Al Rafly, Tegar; Al Ansory, Andre Rahmat; Raihana, Hana; Rahmawati, Nurul 'Ilmi; Tri Utami, Olga (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
Kelurahan Berkas is a coastal area in Teluk Segara Sub-district, Bengkulu Regency, Bengkulu Province. The purpose of this research is to identify the presence of groundwater in Kelurahan Berkas. The method used was resistivity geoelectric method with Wenner-Schlumberger configuration. This research applied three lines, the first in the Southwest-Northeast direction and the second in the East-West direction, with a length of 240 metres each. The results show that the free aquifer layer in the first pass has a resistivity value of 1.61 Ω.m to 3.98 Ω.m at a depth of 7 metres to 24 metres. While the second pass has a resistivity value of 3.17 Ω.m to 9.23 Ω.m at a depth of 8 metres to 36.9 metres and the third pass has a resistivity value of 1.62 Ω.m to 7.05 Ω.m at a depth of 2 metres to 20 metres. The results also show that the lithology of the aquifer layer in the study area is interpreted as clay, sandy clay, and sand. This layer contains groundwater that has been affected by seawater intrusion. The influence of this intrusion causes the groundwater to have a relatively low percentage of salinity so that the groundwater at the research location feels brackish. The existence of seawater intrusion is caused by the kelurahan berkas right on the coast so that the kelurahan berkas community lacks clean water, so the well water becomes brackish, therefore with this research the community can find out the location or point where there is groundwater.